PENDIDIKAN ISLAM DALAM SISTEM PENDIDIKAN NASIONAL (TELAAH EPISTEMOLOGI TERHADAP PROBLEMATIKA PENDIDIKAN ISLAM) - Robiatul Awwaliyah; Hasan Baharun (Jurnal Ilmiah Didaktika, 2018)
This paper presents about Islamic Education in the National Education System. Islamic education is the process of human formation in the direction aspired to Islam, including Indonesia, which is the majority of the population of Muslims. Indonesia with a variety of diversity and potential to improve the quality of education, but can not be denied also can drift in the atmosphere with the diversity, not infrequently it becomes a source of conflict between people. Seeing the reality at the present time, that is increasingly slackening of Islamic values and the actual Eastern adat becomes the identity of our country, is a concrete proof of the failure of Islamic Education as a national education system. If examined more deeply there are some problems that are very necessary to be overcome. To overcome this problematic the State then gives space to Islamic Education by stipulating in the Law of National Education System that Islamic Education has wider authority to contribute in directing human towards the aspired.